Modelling long term digital preservation costs: a scientific data case study - Shehab, Essam; Lefort, Alice; Badawy, Mohamed; Baguley, Paul; Turner, Christopher J.; Wilson, Michael; Conway, Esther (Cranfield University Press, 2013)
In recent years there has been increasing UK Government pressure on publicly funded researchers to plan the preservation and ensure the accessibility of their data for the long term. A critical challenge in implementing a digital preservation strategy is the estimation of such a programme’s cost. This pa-per presents a case study based on the cost estimation of preserving scientific data produced in the ISIS facility based at The Science and Technology Facilities Council (STFC) Rutherford Appleton Laboratory UK. The model for cost estimation for long term digital preservation is presented along with an outline of the development and validation activities undertaken as part of this project. The framework and methodology from this research provide an insight into the task of costing long term digital preservation processes, and can potentially be adapted to deliver benefits to other organisa-tions.
Keywords: Digital Preservation; Curation; Cost Estimation; Whole Lifecycle Cost